Antioxidant Activity of “Kolang Kaling” Jam which is added with “Pucuk Merah” (Syzygium oleana) Fruit Juice - Kesuma Sayuti; Neswati Neswati; Reza Hijra; Effendi Effendi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2020)
“Kolang kaling” is the endosperm of Arenga pinnata seed that contains galactomannan so it can be made into jam. This research was aimed to study the effect of “Pucuk merah” fruit juice as a natural colorant and antioxidant sources on antioxidant activity of the jam. This research used an experimental design with different levels of the juice of “Pucuk merah” fruit (6%, 8%, 10%, and 12%). Observations were anthocyanin level (pH differential method), total phenol (by Follin-Ciocalteu method) and antioxidant activity (by DPPH method) of the jam. It was found that the addition of the concentration level of “Pucuk merah” fruit juice had a statistically significant effect on the anthocyanin and total phenol level of the jam. The more the juice was added, the higher the anthocyanin level (2.82 ± 0.13 ppm; 3.76 ± 0.29 ppm; 3.88 ± 0.11 ppm; and 4.20 ± 0.52 ppm, respectively) and the higher the total phenol level (382 ± 1.53 mg GAE/100g; 431 ± 3.06 mg GAE/100g; 540 ± 1.53 mg GAE/100g and 547 ± 6.43 mg GAE/100g, respectively). By using sensory evaluation, the best product was the addition of 12% of the juice; the antioxidant activity was 628 ppm.